Digital Image Correlation and Reliability-Based Methods for the Design of Structural Beams Made from Recycled Concrete Using Aggregates from Precast Rejects - Jorge López-Rebollo; Evelio Teijón-López-Zuazo; Roberto García-Martin; Luis Javier Sánchez-Aparicio; Diego González-Aguilera (Applied Sciences)
The use of recycled aggregates in the manufacture of concrete is presented as a solution to reduce the consumption of resources and waste in the construction sector and contribute to a lower environmental impact. This work aims to explore the possibility of producing structural beams from recycled concrete using aggregates from precast concrete rejects and to improve their design using advanced characterisation techniques. To this end, the experimental data coming from mechanical test and the use of the digital image correlation approach are combined with a robust reliability-based method. The full-field data provided by the digital image correlation approach allow to determine the probabilistic density functions of the mechanical data. From these data, a predictive analysis of the maximum strength and deflection of flexural beams is carried out based on robust design techniques. This approach uses analytical theoretical models and a Monte Carlo-based simulation strategy that allows the prediction of the behaviour of the beams. This methodology was validated by manufacturing six beams with the previously analysed recycled concrete, HA-30, and testing them in the laboratory. All the beams showed behaviour within the predicted range: around 49.7 kN maximum load and just over 9.3 mm maximum deflection. These results demonstrate the robustness of the approach as well as the feasibility of using precast rejects for the manufacture of structural elements.